2021
DOI: 10.3390/cancers13071736
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial and Mesenchymal Markers in Adrenocortical Tissues: How Mesenchymal Are Adrenocortical Tissues?

Abstract: A clinically relevant proportion of adrenocortical carcinoma (ACC) cases shows a tendency to metastatic spread. The objective was to determine whether the epithelial to mesenchymal transition (EMT), a mechanism associated with metastasizing in several epithelial cancers, might play a crucial role in ACC. 138 ACC, 29 adrenocortical adenomas (ACA), three normal adrenal glands (NAG), and control tissue samples were assessed for the expression of epithelial (E-cadherin and EpCAM) and mesenchymal (N-cadherin, SLUG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
1
4
0
1
Order By: Relevance
“…This indicates that the different members of the pathway have similar expression patterns between the normal and benign adrenocortical tissues but different from the ACC. Interestingly, the expression in all adrenocortical tissues clustered again separately from the expression in other normal and neoplastic tissues of both epithelial and mesenchymal origin indicating that adrenocortical tissues represent a particular tissue type as we could show before ( 43 ). A defining property of FGFs and their receptors is that they bind to heparin and heparan sulfate and are therefore intimately connected with the extracellular matrix of tissues ( 44 ) where they play an important role during epithelial morphogenesis ( 45 ).…”
Section: Discussionsupporting
confidence: 68%
“…This indicates that the different members of the pathway have similar expression patterns between the normal and benign adrenocortical tissues but different from the ACC. Interestingly, the expression in all adrenocortical tissues clustered again separately from the expression in other normal and neoplastic tissues of both epithelial and mesenchymal origin indicating that adrenocortical tissues represent a particular tissue type as we could show before ( 43 ). A defining property of FGFs and their receptors is that they bind to heparin and heparan sulfate and are therefore intimately connected with the extracellular matrix of tissues ( 44 ) where they play an important role during epithelial morphogenesis ( 45 ).…”
Section: Discussionsupporting
confidence: 68%
“…Of note, Sbiera et al showed that in ACC, there is no indication of EMT as all adrenocortical tissues lacked expression of epithelial markers and exhibited closer similarity to mesenchymal tissues. However, higher SLUG expression (mesenchymal marker) was associated with clinical markers indicating aggressiveness [45].…”
Section: Discussionmentioning
confidence: 99%
“…β-Catenin silencing in H295R cells resulted in a decreased proliferation in vitro, abrogated tumor growth in vivo 16 and led to the down-regulation of the transcription factor Slug, 17 which is associated with a more aggressive phenotype of ACC. 18 Besides alterations of the Wnt/β-Catenin signaling pathway, massive deregulations of microRNA (miRNA) expression have been identified in ACC. 8,9,19,20 MiRNAs are small noncoding RNA of about 22 nucleotides-long, 21 which repress their target gene expression at the post-transcriptional level, either by inducing mRNA cleavage, destabilization or inhibition of translation.…”
Section: Introductionmentioning
confidence: 99%